Effect of ethanolic extract of Eucalyptus globulus leaves on growth enhancing, gut morphology, and intestinal absorption capacity in broiler chicken - Ullah, A; Anjum, AA; Raziq, F; Khan, MT; Gul, R; Rauf, M; Wadood, F; Ali, H; Abbas, G; Bughio, E; Younas, U; Nisa, Q; et al. (Journal of the Hellenic Veterinary Medical Society, 2024)
The current trial was designed to evaluate the effects of ethanolic extract of Eucalyptus globulus on growth enhancing effects, and gut morphology on broiler chicks. In 35 days (5 weeks) of feeding trial, a total 75, one-day-old mixed sex broiler chicks (Arbor Acres) (having body weight 45.43±10.00 g) were divided into five groups, e.g. 1 = PC (Positive control), 2 = NC (Negative control), 3 = Prob. (Probiotic), 4 = E. globules powder (EP), and 5 = E. globules extract (EE), having 3 replicates with 15 birds each. Collected data were analysed. In growth performance was measured weekly. While, D-xylose test was performed at 0 min, 30 min, 60 min, 90 min at day last trial day and birds were slaughtered and intestinal gut parts samples were collected, e.g. duodenum, jejunum, and ileum. Results indicated that BWG and FCR at age-day 35 were highest and better in the EE as compared to other groups, respectively. The active and quick D-xylose gut absorption was found in EE as compared to other groups. The histomorphology of gut villi length showed an increase in villi height, width, crypt, and depth. It was evaluated that ethanolic extract of E. globulus can be used in poultry feed to replace low level of antibiotics used as a growth promoter and has role in the fast absorption of nutrients in the gut with enhanced villus height (μm), width (μm), and surface area (μm).